Therapeutic target and molecular mechanism of vitamin C-treated pneumonia: a systematic study of network pharmacology. Issue 5 (18th May 2020) - Li, Rong; Guo, Chao; Li, Yu; Liang, Xiao; Yang, Lu; Huang, Wenjun
Abstract : Vitamin C (VC), a well-reported antioxidant, is found with beneficial actions of preventing and treating pneumonia. Abstract : Vitamin C (VC), a well-reported antioxidant, is found with beneficial actions of preventing and treating pneumonia. However, the detailed pharmacological target and mechanism of VC-treated pneumonia remain unclear. Thus, the present bioinformatics approach using systematic network pharmacology aimed to reveal primary predictive targets, cellular processes, and molecular pathways of VC-treated pneumonia. As shown in bioinformatics assays, the data included 90 primary presumptive targets of VC-treated pneumonia, and 5 other core targets of VC-treated pneumonia were identified as mitogen activated protein kinase 1 (MAPK1), c–c chemokine receptor type 5 (CCR5), mitogen activated protein kinase 3 (MAPK3), angiotensin II type 2 (AT-2) receptor (AGTR2), and signal transducer and activator of transcription 3 (STAT3). In addition, all biological processes (including top 20) and signaling pathways (including top 20) of VC-treated pneumonia were identified and illustrated through bioinformatics analyses. In conclusion, VC-achieved anti-pneumonia effects are mechanically implicated with the suppression of inflammation and enhancement of immunoregulation associated with functional processes and signaling pathways. More interestingly, the identified VC targets may act as biomarkers for the diagnosis and treatment of pneumonia.